(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article carries out the following tasks of the research: to differentiate the peculiarities of English pronunciation, to observe the difficulties in teaching pronunciation, to investigate the process of teaching pronunciation, to develop correct pronunciation by phonetic exercises, to study the influence of intonation, pitch range, tone on the meaning of speech, to investigate the ways of teaching correct pronunciation, to increase the confidence in teaching pronunciation effectively.